Genetic Manipulation of Staphylococcus aureus. Issue 1 (6th February 2014) - Schneewind, Olaf; Missiakas, Dominique
Abstract: Staphylococcus aureus is a facultative anaerobic Gram‐positive coccus and a member of the normal skin flora, as well as that of the nasal passages of humans. However, S. aureus can also gain entry into the host and cause life‐threatening infections or persist as disease foci that develop into suppurative abscesses. While genetically tractable, the manipulation of S. aureus remains challenging. This unit describes methods developed in our laboratory for gene disruption by allelic replacement and transposition. We also provide a protocol for bacteriophage‐mediated transduction of mutants marked with selectable alleles and describe plasmid utilization for complementation studies. Curr. Protoc. Microbiol . 32:9C.3.1‐9C.3.19. © 2014 by John Wiley & Sons, Inc.